Characterization of brushed DC motor with brush fault using thermal assessment - Abbas, Abdul Wahab; Mohd Azri Hizami, Rasid (Institute of Physics Publishing, 2020)
Direct current motors (DC motor) are used in the small electric devices commonly. Brushed DC motors are cheap and easy to install, thus their popularity. Although the popularity, faults occur which make diagnosis and detection of faults very important. It avoids financial loss and unexpected shutdown operation causes by these faults. This paper is a present characterization of brushed DC motor with brush fault using thermal signature analysis. To organize the character, the temperature profile of DC motor was analysed using the K-type thermocouple with data logger. The thermocouples were mounted on 4 part of the DC motor, casing, permanent magnet, brush and bearing. The temperature data of DC motor with faulty brush and healthy DC motor were measured by thermocouple and recorded using data logger in real time until steady state temperature, under different load. The analysis on the steady state temperature of brush fault can be conclude through recognisable of characteristics temperature difference with a healthy motor.